Delivering proportionate governance in the era of eHealth: Making linkage and privacy work together. (June 2013) - Sethi, Nayha; Laurie, Graeme T.
This article advances a principled proportionate governance model (PPGM) that overcomes key impediments to using health records for research. Despite increasing initiatives for maximising benefits of data linkage, significant challenges remain, including a culture of caution around data sharing and linkage, failure to make use of flexibilities within the law and failure to incorporate intelligent iterative design. The article identifies key issues for consideration and posits a flexible and accessible governance model that provides a robust and efficient means of paying due regard to both privacy and the public interests in research. We argue that proportionate governance based on clear guiding principles accurately gauges risks associated with data uses and assigns safeguards accordingly. This requires a clear articulation of roles and responsibilities at all levels of decision-making and effective training for researchers and data custodians. Accordingly, the PPGM encourages and supports defensible judgements about data linkage in the public interest.